Effect of cement grouts containing irradiated polyethylene terephthalate on properties of semi-flexible mixtures - Khan, M.I. (Trans Tech Publications Ltd, 2021)
The semi-flexible pavement surface is a hybrid type of pavement surface which combines the effect of both asphalt mix skeleton and cement grout. The current study investigates the influence of cement grouts containing irradiated waste polyethylene terephthalate (PET) on the performance of semi-flexible mixtures. The ordinary Portland cement was partially replaced by regular and irradiated PET as well as with fly ash (FA) in cement grouts. The semi-flexible mixtures, containing waste PET and FA, were evaluated for air voids analysis, degree of grout saturation, Marshal stability, indirect tensile strength (ITS) and tensile strength ratio (TSR) of semi-flexible specimens. The semi-flexible mixtures showed superior performance in terms of strength properties. The results indicate that with the irradiation process, more waste PET (almost double) can be recycled as compared to regular waste PET in cement grouts for semi-flexible pavement surfaces. This approach will lead to a sustainable solution for recycling waste PET in highway materials for the construction of a hybrid type of pavement surface. Â© 2021 Trans Tech Publications Ltd, Switzerland.